Stratigrafi Di Barat Daya Sabah (The Stratigraphy of Southwest Sabah) - Tracy binti Guan Leong; Sanudin Hj. Tahir; Junaidi Asis (2018)
This study is aimed to study the stratigraphy in southwest Sabah. The study area consists of Temburong Formation, Crocker Formation, Meligan Formation and Liang Formation. Through the study, the Temburong Formation was found to be underlying the Crocker Formation in terms of stratigraphic sequence position which has been considered otherwise. This means that the position of stratigraphic sequence of Temburong Formation which was previously considered to be above the Crocker Formation is now being interpreted below the Crocker Formation. Facies analysis, facies association studies, cross-sectional studies, litostratigraphic studies, and correlation of litostratigraphic units in the study area helped to interpret the stratigraphy and update the position of stratigraphy for the Paleogene sequences. The Temburong Formation and Crocker Formation are both dated as Upper Eocene to Lower Miocene while the Meligan Formation is Middle Miocene to Upper Miocene and Liang Formation is Pliocene.